2014
DOI: 10.1155/2014/124974
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic Effect of Tetracarpidium Conophorum Nuts in Alloxan Induced Diabetic Female Albino Rats

Abstract: The antihyperglycaemic activity of Tetracarpidium conophorum nut (walnut) was investigated in albino rats. A total of 20 albino rats were used for the study. The rats were divided into five groups (A–E) of four rats each. Diabetes were induced in the rats except four which served as the positive control group A. Groups B (negative control), C, D, and E contain diabetic rats each with blood sugar level ≥17.00 mmol/L. Groups A and B were fed on 85.2 g of top feed grower over the test period. Test groups C, D, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…In the present study, increased urine output was observed in diabetic control animals which are in line with previously published report [15] . Treatment with OJ, Metformin and OJ-Metformin combination caused significant reduction in urine output.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, increased urine output was observed in diabetic control animals which are in line with previously published report [15] . Treatment with OJ, Metformin and OJ-Metformin combination caused significant reduction in urine output.…”
Section: Discussionsupporting
confidence: 94%
“…Similar alterations in the serum lipid of the animals suggested cardiovascular risk and that it was not completely safe for consumption. Onwuli, Bown and Ozoani (2014) and Ogunyinka et al (2015) reported that the nuts have the potential to reduce hyperglycaemia; the authors also reported that the nuts increased the haemoglobin level and decreased urine output in the test group when compared with controls and could prevent diabetes associated with renal damage.…”
Section: Anti-ulcer and Wound Healing Activitiesmentioning
confidence: 98%
“…The consumption of 85.2 g of walnuts from 40 male rats with increased blood glucose level for 2 weeks reduced the blood glucose levels [21]. In a randomized control trial for 12 weeks the consumption of 30 g/day of cashew nuts from 300 adults with type II diabetes, increased HDL cholesterol, body weight, BMI, waist circumference, and decreased systolic blood pressure [76].…”
Section: Recent Data About the Possible Effect Of Specific Functiomentioning
confidence: 99%